2017
DOI: 10.1016/j.foreco.2017.06.038
|View full text |Cite
|
Sign up to set email alerts
|

Pinus halepensis M. versus Quercus ilex subsp. Rotundifolia L. runoff and soil erosion at pedon scale under natural rainfall in Eastern Spain three decades after a forest fire

Abstract: Afforestation aims to recover the vegetation cover, and restore natural ecosystems. The plant species selected for restoration will determine species richness and the fate of the ecosystem. Research focussing on the impact of vegetation recovery on soil quality are abundant, especially on fire affected land and where rehabilitation, afforestation and restoration projects were carried out. However, little is known about how different plants species affect soil erosion and water losses, which are key factors tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(26 citation statements)
references
References 90 publications
0
25
0
1
Order By: Relevance
“…The runoff initiation threshold that is used to describe the rainfall retention capacity and runoff initiation should be high in the forested areas due to the high interception and soil permeability. For example, Cerdà, Borja, Úbeda, Martínez‐Murillo, and Keesstra () demonstrated that the threshold for initiating runoff in Aleppo pine and Holm oak plantation in Mediterranean area could be up to ~18 and ~30 mm, whereas the threshold was only ~10.0 mm in our plots (Figure a).…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…The runoff initiation threshold that is used to describe the rainfall retention capacity and runoff initiation should be high in the forested areas due to the high interception and soil permeability. For example, Cerdà, Borja, Úbeda, Martínez‐Murillo, and Keesstra () demonstrated that the threshold for initiating runoff in Aleppo pine and Holm oak plantation in Mediterranean area could be up to ~18 and ~30 mm, whereas the threshold was only ~10.0 mm in our plots (Figure a).…”
Section: Discussionmentioning
confidence: 65%
“…The low threshold of runoff initiation and low RC characterized the rainfall–runoff behavior in this high‐rainfall region. Conceptually, the threshold of runoff initiation in forest area should be high (Cerdà et al, ), because the intense precipitation might exceed the infiltration capacity and generate infiltration excess resulting in overland flow quickly (Castillo, Gomez‐Plaza, & Martinez‐Mena, ). However, the quite low threshold of runoff imitation in our forested cases may reflect the abundant rainfall.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies should specifically focus on intrinsic changes in the carbon cycle [93], the role of soils in the earth cycles [94] and the soil erosion cycle [95]. Additionally, most research carried out on forest fires has investigated plant composition, soil properties, soil erosion and runoff generation, and the restoration of soil and vegetation cover after fire [96][97][98][99][100][101]. Little attention was instead paid to identify the causes and the spatial distribution of forest fires, demonstrating, for example, that roads are a serious source of ignition.…”
Section: Discussionmentioning
confidence: 99%
“…This variations of soil erosion could largely be attributed to the different erosion mechanism from splash (micro‐plot scale) to interrill (plot scale). The micro‐plot had a short slope length, important when identifying homogeneous soil patches that are usually dominated by raindrop detachment of soil particles and splash transport erosion mechanisms (Cerdà et al, ). Bagarello et al .…”
Section: Discussionmentioning
confidence: 99%